Numerical study on landslide dynamic process and its impact damage prediction to brick-concrete buildings, a case from Fenghuang street landslide in Shaanxi, China - Zhao, Zhou; Chen, Xing; Wei, Jiangbo; Ma, Jianquan; Ye, Wanjun (Frontiers in Earth Science, 2023)
The study on landslide movement and its impact intensity has significant theoretical and practical implications for predicting and quantitatively assessing of landslide risk. In this paper, on the basis of field investigation and landslide exploration data analysis, combined with a geotechnical test, the three-dimensional numerical model of the Fenghuang Street landslide is constructed using the particle flow discrete element method. The simulation of the whole process of landslide instability failure, movement accumulation, and impact is performed in advance, and the quantitative study of dynamic indexes such as velocity, displacement, and impact force of the landslide body during movement is conducted. According to the impact force, the model of the house in front of the slope is produced using the particle flow software (PFC3D) and the finite element software (Midas/gen). The characteristics of deformation and stress distribution of the buildings after the impact of the landslide are analyzed, and then the impact intensity of the landslide is predicted. The results indicate that the deformation and failure of the rear edge of the landslide occur first, and the soil in front is pushed step by step, and when the locking section of the leading edge passes through, the landslide begins to slide as a whole, which is a typical push landslide, the main sliding time of the landslide is about 30s, the maximum average velocity is 3.2m/s, and the maximum displacement is about 40m. After the impact of the landslide, the displacement of the building at the foot of the landslide extends forward and upward, and the impact surface of the building is destroyed, resulting in an evident collapse. The relevant research methodologies and findings of this paper can serve as a reference for the risk assessment of the same type of landslides, particularly for the quantitative assessment of vulnerability for the buildings at landslide risk.